2016
DOI: 10.5507/bp.2016.041
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin is more likely to be released by the fetus rather than placental tissue during chorioamnionitis

Abstract: Aims. To analyze the relationship between maternal, cord blood and neonatal procalcitonin (PCT) levels in preterm deliveries with and without histologically proven chorioamnionitis (HCA). Methods. 91 mother-infant pairs from 24+0 to 33+0 gestational weeks were analyzed. Procalcitonin was measured in all mothers within 24 hours before and subsequently in cord blood and in neonates within the first two hours after delivery. PCT levels were analysed in relationship to HCA and clinical outcome. Results. HCA was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…found that the maternal blood PCT level in the vaginal delivery group was higher than that in the cesarean section group, which is contrary to the results of Paccolat et al .’s study . In the present study, we found that the delivery method did not affect umbilical cord blood PCT level, which indirectly indicated that umbilical cord blood PCT and maternal blood PCT came from different sources …”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…found that the maternal blood PCT level in the vaginal delivery group was higher than that in the cesarean section group, which is contrary to the results of Paccolat et al .’s study . In the present study, we found that the delivery method did not affect umbilical cord blood PCT level, which indirectly indicated that umbilical cord blood PCT and maternal blood PCT came from different sources …”
Section: Discussionsupporting
confidence: 52%
“…PCT is highly sensitive and specific in the diagnosis of infection, and thus it is considered as a promising biochemical marker for early infection detection, inflammation estimation and prognosis prediction . maternal serum and neonatal cord blood PCT have been used by some researchers in intrauterine infection‐related studies . Chorioamnionitis (CA), which is an inflammation of fetal membranes, amniotic fluid, placenta and/or decidua, is the most common cause of intrauterine infection .…”
Section: Introductionmentioning
confidence: 99%
“… 3 Changes in PCT values in cord and neonatal blood in proven histological chorioamnionitis suggest its production and release by fetal tissue. 4 Another study in neonatal and umbilical cord blood was related to intrauterine infection and useful to predict infection in the newborn infant. 5 In another study of umbilical cord blood samples, both interleukin (IL)-6 and PCT were reliable as a rule-in and a rule-out tool for neonatal sepsis, whereas IL-6 was useful in neonates.…”
Section: Introductionmentioning
confidence: 99%
“…Sepsis and CAM are among the most devastating causes of neonatal morbidity and mortality, and the prediction and early diagnosis of neonatal sepsis and CAM are very important for neonatal care . To date, several reports have been made on the usefulness of umbilical venous PCT, mainly for two purposes: the prediction of neonatal sepsis and the early diagnosis of CAM .…”
Section: Discussionmentioning
confidence: 99%